Improving Speech Writing Skills Through Mind Mapping Of Class Vi Students Of SDN 004 Kabun - Ratna Mawan Sibuea (STKIP Rokania Pasir Pangaraian, 2022)
This research is motivated by students who are not yet skilled in writing speech texts with systematic and effective language. This is caused by several factors such as the lack of knowledge of students about linguistic elements in writing so that the writings produced by students are not in accordance with the applicable grammatical rules. In addition, teachers have not been able to develop an active, innovative, creative, effective, and fun learning atmosphere in learning. This causes students to lose their motivation and passion to learn to write. The results showed that mind mapping which is used as a learning tool can improve students' activities and learning outcomes in writing speech texts. The learning process with the help of mind mapping helps students generate main ideas and explanatory ideas, and connects these ideas in coherent and coherent sentences. Thus, learning to write speech texts through mind mapping makes students think critically, logically, and systematically